2004
DOI: 10.1002/bio.780
|View full text |Cite
|
Sign up to set email alerts
|

The forensic use of luminol chemiluminescence to detect traces of blood inside motor vehicles

Abstract: The luminol test for blood was carried out on a set of interior fittings and surfaces inside three different makes of modern motor car. The surfaces and fittings provided little interference with the test for blood, although there was some detectable chemiluminescence when the test was applied to blood-free material from a seatbelt, a boot-lining and a gear-knob. The case with which haemoglobin samples could be washed off interior car surfaces was also examined for seat fabrics, carpets, roof-linings and vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…A análise do padrão das manchas de sangue como a distribuição, forma, contorno e tamanho pode substancialmente contribuir na reconstrução de eventos em cenas do crime [11]. O luminol se mostrou eficiente mesmo quando a quantidade de sangue é diminuta [12] como no caso da parede analisada.…”
Section: Discussionunclassified
“…A análise do padrão das manchas de sangue como a distribuição, forma, contorno e tamanho pode substancialmente contribuir na reconstrução de eventos em cenas do crime [11]. O luminol se mostrou eficiente mesmo quando a quantidade de sangue é diminuta [12] como no caso da parede analisada.…”
Section: Discussionunclassified
“…During the investigation of some types of the crime scenes, a need to search for some biological evidence such as blood is likely to occur [9]. When found, blood traces are documented by forensic technicians with a camera.…”
Section: Searching For Bloodmentioning
confidence: 99%
“…After this period the intensity of the illumination is too weak to notice. Due to the fact that the luminol solution reacts only with a part of the blood cell components, the discovered blood can be afterwards used for ABO blood group tests [9,[11][12][13]. Negative aspects of the use of the luminol solution in the process of searching for the blood stains are related to the nature of the oxidation process and the interferences of some chemical compounds.…”
Section: Searching For Bloodmentioning
confidence: 99%
“…Although the classical luminol protocols by Grodsky and Weber are good enough in most cases, some attempts were made recently to improve the reaction , in several instances the final results being applied in commercially available kits.…”
mentioning
confidence: 99%
“…In 2004, Quickenden et al noticed that blood stains which are found in vehicles gave a stronger luminescence with luminol compared to the blood stains from outside the vehicles. They suggested that methemoglobin was involved in this enhancement process, as Fe 2+ oxidation could occur faster in a warmer environment.…”
mentioning
confidence: 99%